A Hybrid Peptide DEFB-TP5 Expressed in Methylotrophic Yeast Neutralizes LPS With Potent Anti-inflammatory Activities - Ahmad, Baseer; Li, Zhongxuan; Hanif, Quratulain; Hu, Qingyong; Wei, Xubiao; Zhang, Lulu; Khan, Shahzad Akbar; Aihemaiti, Maierhaba; Gulzar, Huma; Shahid, Muhammad; Si, Dayong; Zhang, Rijun (Frontiers in Pharmacology, 2020)
DEFB-TP5 is a novel promising health-beneficial peptide derived from two naturally occurring peptides, β-Defensin (DEFB) and thymopentin (TP5), shows strong anti-inflammatory activity and binds to LPS without cytotoxicity and hemolytic effect. However, the application of DEFB-TP5 peptide is limited by its high cost. In this study, we developed a biocompatible mechanism for expression of the DEFB-TP5 peptide in Pichia pastoris. The transgenic strain of hybrid DEFB-TP5 peptide with a molecular weight of 6.7kDa as predictable was obtained. The recombinant DEFB-TP5 peptide was purified by Ni-NTA chromatography, estimated 30.41 mg/L was obtained from the cell culture medium with 98.2% purity. Additionally, The purified DEFB-TP5 peptide significantly (p< 0.05) decreased the release of nitric oxide (NO), TNF-α IL-6, IL-1β in LPS-stimulated RAW264.7 macrophages in a dose-dependent manner. This study will not only help to understand the molecular mechanism of expression that can potentially be used to develop an anti-endotoxin peptide but also to serve as the basis for the development of antimicrobial and anti-inflammatory agents as well, which also provides a potential source for the production of recombinant bioactive DEFB-TP5 at the industrial level.